1996
DOI: 10.1007/bf02355061
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic colitis during interferon-alpha treatment for chronic active hepatitis C

Abstract: Between 1991 and 1994, at Hoshigaoka Koseinenkin Hospital, we treated 280 patients with chronic hepatitis C with interferon (IFN), and ischemic colitis occurred in two patients (0.7%) during the treatment. Melena appeared in case 1 in the 2nd month after the initiation of IFN-alpha treatment, and in case 2 in the 6th month. In both patients, longitudinal ulcerations in the descending colon were revealed by urgent colonoscopy, and these resolved within 2 weeks after discontinuation of the IFN treatment. It appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 14 publications
2
16
0
1
Order By: Relevance
“…In spite of the clinical improvement achieved by a high proportion of patients with HCV-associated mixed cryoglobulinemia treated with IFN␣, most reported series include a minority of patients in whom vasculitic manifestations worsen in association with IFN␣ treatment (4). Moreover, the development of ischemic lesions during IFN␣ therapy for other conditions has also been reported (5,6). Careful followup of our patients revealed that cryoglobulinemic ulcers became progressively devoid of vascularization and granulation tissue, with subsequent appearance of necrosis and bacterial colonization.…”
Section: Discussionsupporting
confidence: 75%
“…In spite of the clinical improvement achieved by a high proportion of patients with HCV-associated mixed cryoglobulinemia treated with IFN␣, most reported series include a minority of patients in whom vasculitic manifestations worsen in association with IFN␣ treatment (4). Moreover, the development of ischemic lesions during IFN␣ therapy for other conditions has also been reported (5,6). Careful followup of our patients revealed that cryoglobulinemic ulcers became progressively devoid of vascularization and granulation tissue, with subsequent appearance of necrosis and bacterial colonization.…”
Section: Discussionsupporting
confidence: 75%
“…It has been reported that approximately 60% of patients with chronic hepatitis or cancer treated with Roferon have intestinal disorders, especially diarrhea. Case reports also note rare cases of pseudoinflammatory bowel disease subsequent to IFN alpha/ribavirin treatment for chronic hepatitis 27, 28…”
Section: Discussionmentioning
confidence: 99%
“…Multiple anecdotal case reports and case series have described associations of ischaemic colitis with vascular surgery and vascular thromboembolism, 4-7 co-morbid medical conditions [8][9][10][11][12][13][14][15][16][17][18] and medications including vasoconstrictors, psycho-tropics, oral contraceptives, interferon-a and 5-hydroxytryptamine-1 (5-HT 1 ) agonists (triptans). [19][20][21][22][23][24][25] Transient ischaemic colitis was first reported as a clinical finding in the 1960s by Boley et al 26 and Marston et al 27 It has since become a well-recognized clinical entity, with well-characterized endoscopic 28 and pathological 29 findings. Ischaemic colitis has recently become the subject of great controversy, as a new class of medications (5-HT 3 antagonists) has been associated with this condition, 30 leading to the initial withdrawal by the Food and Drug Administration, and later restoration, of alosetron to the market in the USA.…”
Section: Introductionmentioning
confidence: 99%